Pengaruh Pengendalian Internal Terhadap Perilaku Etis Karyawan dalam Sistem Penggajian - Sri Astuty Ratnasari; Wahyu Maulid Adha (Journal of Economic, Public, and Accounting (JEPA), 2019)
This study aims to determine the effect of internal control on employees ethical behavior in the payroll system at the Regional Water Company of Majene Regency. The data used are primary data in the form of questionnaires distributed to employees and conducted interviews at the Regional Water Company of Majene Regency. The results showed that the independent variables (internal control) have a significant effect on the dependent variable (Ethical Conduct Employees in Payroll System). This is proved by a simple regression analysis obtained value of R Square of 0.266, which means that the influence of internal control over ethical behavior of employees is 26.6% and the remaining 73.4% is influenced by other variables. Based on the results of significant value, the results are less than the level of significant is 0.002 <0.05. In addition, it can be seen also from the comparison tcountand ttable. Based on the results obtained output SPSS version 16 tcountat 3,339 while ttablevalue of 2.051. Due tcountgreater than 3,339 ttable> 2.051 hypothesis (H1) is accepted. So we can conclude that internal controls have a positive and significant influence on the ethical behavior of employees. This means more and better internal control better the ethical behavior of employees in the payroll system.And based on the results of interviews with one of the employees as treasurer salary PDAM Majene stated that the salary system applied in the company is running well and ethical behavior of employees who do not comply with the rules set in the company will be given sanctions or punishment in the form of not getting promotion and can be removed . This means the better the internal control the better the ethical behavior of employees in the payroll system